اجراءات السالمة في المنشآت النفطية )دراسة ميدانية بالرصيف النفطي بميناء المنطقة الحرة مصراته( (Comprehensive Journal of Science, 2025)
This research aims to study the current occupational safety and environmental proceduresimplemented at the oil port of Misurata, and analyze the effectiveness in reducing industrialaccidents and oil spills, which are among the main threats to the safety of workers and thesurrounding marine environment. The study addressed the main sources of risk within the port, suchas oil leaks from pipelines and oil tankers, and the impact of the absence or weak enforcement ofsafety procedures on increasing the likelihood of these incidents.The research adopted a descriptive-analytical approach, where data was collected through fieldvisits, direct observations, interviews with workers, and analysis of relevant documents and reports.The study concluded that there is a disparity in the implementation of safety procedures betweenmanagerial and technical levels, and there is an urgent need to enhance safety culture, updateemergency prevention and response systems, and intensify practical training for workers.
Keywords: Occupational Safety, Misurata Oil Port, Marine Environment), Prevention Systems